Resin bonding to a hybrid ceramic: Effects of surface treatments and aging - Campos, F. [UNESP]; Almeida, C. S. [UNESP]; Rippe, M. P.; De Melo, R. M. [UNESP]; Valandro, L. F.; Bottino, M. A. [UNESP] (Operative Dentistry, 2016)
The aim of this study was to verify the effects of different surface treatments on the microtensile bond strength between resin cement and a hybrid ceramic. Thirty-two hybrid ceramic slices (831033 mm) were produced and allocated among four groups according to the surface treatment: Cont = no treatment, HA = 10% hydrofluoric acid applied for 60 seconds, PA = 37% phosphoric acid applied for 60 seconds and CJ = air abrasion with silica particle coated alumina (Cojet Sand, 3M ESPE, 30 lm/2.8 bar). As a control group, eight blocks of feldspathic ceramic (8 3 10 3 3 mm) were etched by hydrofluoric acid for 60 seconds (VMII). After the surface treatments, the ceramic slices were silanized (except the Cont group) and adhesively cemented to composite resin blocks (831033 mm ) with a load of 750 g (polymerized for 40 seconds each side). The cemented blocks were cut into beams (bonded surface area of ;1 mm2 ). Half of the beams were aged (thermocycling of 58C-558C/6000 cy-cles + water storage at 378C/60 days), and the other half were tested immediately after being cut. Data were analyzed by Kruskal-Wallis and Dunn tests (non-aged groups) and by one-way analysis of variance and Tukey test (aged groups; a=0.05%). The mode of failure was classified by stereomicroscopy. The surface treatment significantly affected the bond strength in each set of groups: non-aged (p=0.001) and aged (p=0.001). Before being aged, samples in the CJ, HA, and PA groups achieved the highest bond strength values. However, after being aged, only those in the HA group remained with the highest bond strength values. Adhesive failure was found most often. In conclusion, hydrofluoric acid etching should be used for surface conditioning of the studied hybrid ceramic.